Gastrocolic fistula as a complication of percutaneous endoscopic gastrostomy (PEG): a case report and review of literature - Kishore, Anand (International Surgery Journal, 2018)
Gastrocolic fistula is a rare complication which is seen after percutaneous endoscopic gastrostomy (PEG). It usually manifest as a late complication. Interesting fact is that gastrocolic fistula is formed during the initial insertion of PEG tube itself but goes unrecognized. It becomes evident only when a tube replacement is done or when tube dislodgement occurs. We report a case where gastrocolic fistula was recognized after 1 month of tube feeding. Aim of our case report is to make clinicians aware of this rare condition and to have high clinical suspicion regarding possible complications of PEG even after a long period of uncomplicated feeding.